2019
DOI: 10.4143/crt.2018.031
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Promote the Chemo-resistance in Gastric Cancer through Secreting IL-11 Targeting JAK/STAT3/Bcl2 Pathway

Abstract: Our results demonstrated that IL-11 contributed to the obtain of resistance to chemotherapy drugs through gp130/JAK/STAT3/Bcl2 pathway, and targeting the IL-11 signaling pathway induced by fibroblasts might be a promising strategy to overcome the multi-drugs resistant cancer in clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…Similar results were observed for oxaliplatin [168]. In vitro studies revealed that IL-11 increased chemoresistance through gp130/JAK/STAT3/BCL-2-mediated anti-apoptosis signaling pathway [169].…”
Section: Mechanisms Of Chemoresistance Type 6 (Moc-6)supporting
confidence: 80%
“…Similar results were observed for oxaliplatin [168]. In vitro studies revealed that IL-11 increased chemoresistance through gp130/JAK/STAT3/BCL-2-mediated anti-apoptosis signaling pathway [169].…”
Section: Mechanisms Of Chemoresistance Type 6 (Moc-6)supporting
confidence: 80%
“…Knockdown of IL-11 in pancreatic cancer cell lines resulted in reduced expression of MMP2 and MMP9 and a 50% reduction in invasive capacity [200]. These results suggest that IL-11 may have a pro-tumorigenic effect in pancreatic cancer, similar to its roles in colorectal [201], gastric [202], and breast [203] cancers.…”
Section: Il-11 May Have a Pro-tumorigenic Role In Pdacmentioning
confidence: 75%
“…Studies have demonstrated that the JAK/STAT3 signaling pathway contributes to cell survival and chemotherapeutic resistance in cancers [ 23 , 24 ]. Furthermore, it enhances the development of CSC-like characteristics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%